2022
DOI: 10.3390/cancers14205048
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot-Based Screening Identifies F3 Peptide and Reveals Cell Surface Nucleolin as a Therapeutic Target for Rhabdomyosarcoma

Abstract: Active drug delivery by tumor-targeting peptides is a promising approach to improve existing therapies for rhabdomyosarcoma (RMS), by increasing the therapeutic effect and decreasing the systemic toxicity, e.g., by drug-loaded peptide-targeted nanoparticles. Here, we tested 20 different tumor-targeting peptides for their ability to bind to two RMS cell lines, Rh30 and RD, using quantum dots Streptavidin and biotin-peptides conjugates as a model for nanoparticles. Four peptides revealed a very strong binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…A high cytoplasmic expression of NCL is associated with a poor prognosis of patients with breast cancer, endometrial carcinoma, gastric cancer and non-small cell lung cancer (24,25,29,30) whereas a high nuclear expression of NCL is an independent good prognostic marker in gastric cancer, endometrial carcinoma and pancreatic ductal adenocarcinoma (17,24,25) (Table I). However, the surface NCL has been linked to the poor survival of patients with gastric cancer, rhabdomyosarcoma, breast cancer, hepatocellular carcinoma, colon cancer and prostate cancer (26,(31)(32)(33) (Table I). In agreement with the rational of a decrease in cell surface NCL expression or activity, several in vitro and in vivo studies showed that decreases in cell surface NCL expression or activity inhibited the growth of cancer cells and triggered apoptosis (34,35).…”
Section: Nucleolin-based Targeting Strategies In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A high cytoplasmic expression of NCL is associated with a poor prognosis of patients with breast cancer, endometrial carcinoma, gastric cancer and non-small cell lung cancer (24,25,29,30) whereas a high nuclear expression of NCL is an independent good prognostic marker in gastric cancer, endometrial carcinoma and pancreatic ductal adenocarcinoma (17,24,25) (Table I). However, the surface NCL has been linked to the poor survival of patients with gastric cancer, rhabdomyosarcoma, breast cancer, hepatocellular carcinoma, colon cancer and prostate cancer (26,(31)(32)(33) (Table I). In agreement with the rational of a decrease in cell surface NCL expression or activity, several in vitro and in vivo studies showed that decreases in cell surface NCL expression or activity inhibited the growth of cancer cells and triggered apoptosis (34,35).…”
Section: Nucleolin-based Targeting Strategies In Cancer Treatmentmentioning
confidence: 99%
“…It also plays a critical role in anti-apoptosis (70) associated with chemoresistance in B-cell lymphoma (70), cervical cancer (81), breast cancer (82) and acute lymphoblastic leukemia (83). Several studies have described the development of molecules that target NCL on the cell surface of cancer cells to suppress or block NCL, and thereby inhibit cancer cell proliferation, apoptosis and angiogenesis (15,26,(31)(32)(33)47).…”
Section: Therapeutic Strategies Exploiting Ncl-based Targetingmentioning
confidence: 99%